Water: The Looming Crisis in India - Ray, Binayak (Lexington Books, 2008)
Water: The Looming Crisis in India analyzes the key issues in developing national freshwater policies for the mainland countries of the South Asian sub-continent. Ray suggests that freshwater policy must cover all aspects of physical environment and human life, by noting that food and drought management are parts of freshwater policy and acknowledging that water is a scarce natural resource and has economic value. He calls for the development of basin-wide policies to minimize conflicts within riparian countries, as well as a freshwater policy baseline to minimize internal conflicts on water sharing arrangements. By pointing out the need for full participation of all stakeholders in developing a baseline policy including people displaced by the construction of large dams, Ray suggests a new system in which riparian countries are guaranteed that no water-related project proceeds without a transparently developed environmental impact assessment and evaluation of alternative options.